The ameliorating effect of withaferin A on high-fat diet-induced non-alcoholic fatty liver disease by acting as an LXR/FXR dual receptor activator - Varsha D. Shiragannavar; Nirmala G. Sannappa Gowda; Lakshana D. Puttahanumantharayappa; Shreyas H. Karunakara; Smitha Bhat; Shashanka K. Prasad; Shashanka K. Prasad; Divya P. Kumar; Prasanna K. Santhekadur (Frontiers Media S.A., 2023)
Introduction: Non-alcoholic fatty liver disease (NAFLD) incidence has been rapidly increasing, and it has emerged as one of the major diseases of the modern world. NAFLD constitutes a simple fatty liver to chronic non-alcoholic steatohepatitis (NASH), which often leads to liver fibrosis or cirrhosis, a serious health condition with limited treatment options. Many a time, NAFLD progresses to fatal hepatocellular carcinoma (HCC). Nuclear receptors (NRs), such as liver X receptor-α (LXR-α) and closely associated farnesoid X receptor (FXR), are ligand-inducible transcription factors that regulate various metabolism-associated gene expressions and repression and play a major role in controlling the pathophysiology of the human liver. Withaferin A is a multifaceted and potent natural dietary compound with huge beneficial properties and plays a vital role as an anti-inflammatory molecule.Methods:In vivo: Swill albino mice were fed with western diet and sugar water (WDSW) for 12, 16, and 20 weeks with suitable controls. Post necropsy, liver enzymes (AST, ALT, and ALP) and lipid profile were measured by commercially available kits using a semi-auto analyzer in serum samples. Liver histology was assessed using H&E and MTS stains to check the inflammation and fibrosis, respectively, using paraffin-embedded sections and mRNA expressions of these markers were measured using qRT-PCR method. TGF-β1 levels in serum samples were quantified by ELISA. In vitro: Steatosis was induced in HepG2 and Huh7 cells using free fatty acids [Sodium Palmitate (SP) and Oleate (OA)]. After induction, the cells were treated with Withaferin A in dose-dependent manner (1, 2.5, and 5 μM, respectively). In vitro steatosis was confirmed by Oil-Red-O staining. Molecular Docking: Studies were conducted using Auto Dock Vina software to check the binding affinity of Withaferin-A to LXR-α and FXR.Results: We explored the dual receptor-activating nature of Withaferin A using docking studies, which potently improves high-fat diet-induced NAFLD in mice and suppresses diet-induced hepatic inflammation and liver fibrosis via LXR/FXR. Our in vitro studies also indicated that Withaferin A inhibits lipid droplet accumulation in sodium palmitate and oleate-treated HepG2 and Huh7 cells, which may occur through LXR-α and FXR-mediated signaling pathways. Withaferin A is a known inhibitor of NF-κB-mediated inflammation. Intriguingly, both LXR-α and FXR activation inhibits inflammation and fibrosis by negatively regulating NF-κB. Additionally, Withaferin A treatment significantly inhibited TGF-β-induced gene expression, which contributes to reduced hepatic fibrosis.Discussion: Thus, the LXR/ FXR dual receptor activator Withaferin A improves both NAFLD-associated liver inflammation and fibrosis in mouse models and under in vitro conditions, which makes Withaferin A a possibly potent pharmacological and therapeutic agent for the treatment of diet-induced NAFLD.